2021
DOI: 10.9745/ghsp-d-20-00556
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Contraceptive Method Choice With a Hormonal Intrauterine System: Results From Mixed Methods Studies in Kenya and Zambia

Abstract: Although the hormonal intrauterine system has limited availability in low- and middle-income countries, this highly effective long-acting reversible contraceptive method has the potential to be an important addition to the method mix. Introduction of the method in the public sector under “real-world” conditions in Kenya and Zambia shows promise to increase contraception use and continuation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 28 publications
(32 reference statements)
1
15
0
Order By: Relevance
“…Similar to findings from another hormonal IUD pilot program in the region [ 17 ], qualitative interviews indicate that some women may not be willing to try a method they are hearing about for the first time. Since the hormonal IUD was relatively new in Zambia, it is not surprising that many women learned about this method from providers.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Similar to findings from another hormonal IUD pilot program in the region [ 17 ], qualitative interviews indicate that some women may not be willing to try a method they are hearing about for the first time. Since the hormonal IUD was relatively new in Zambia, it is not surprising that many women learned about this method from providers.…”
Section: Discussionsupporting
confidence: 53%
“…Initial efforts to introduce the hormonal IUD in Zambia can provide valuable learnings that can inform broader method introduction in Zambia and other countries. A recent pilot study of hormonal IUD introduction with postpartum and postabortion care clients in four provinces in Zambia found high satisfaction and continuation rates among users, with providers also reporting generally high satisfaction among women trying the method [ 17 ]. However, existing evidence on uptake of the hormonal IUD among the general population in public sector settings remains limited.…”
Section: Introductionmentioning
confidence: 99%
“… 15 An observational study, focusing on the post-partum period, reported that 86% of hormonal intrauterine device users interviewed 3–6 months after insertion in Kenya, and 79% of those interviewed in Zambia with an average time of 10 months after insertion were still using this method. 16 Qualitative data in Kenya, Nigeria, and Zambia suggest that key opinion leaders, providers, and users recognise the advantages of the hormonal intrauterine device, and support its inclusion in the contraceptive method mix. 17 , 18 , 19 In this study, we therefore aimed to expand the knowledge about the use of the hormonal intrauterine device, copper intrauterine device, and subdermal implant by measuring continuation rates at 6 months and 12 months and assessing women's experiences and satisfaction using these methods in sub-Saharan Africa in the private sector in Nigeria and the public sector in Zambia.…”
Section: Introductionmentioning
confidence: 99%
“…Offering youth a full range of contraceptive options, including long-acting and reversible contraceptives (LARCs) through adolescent-friendly contraceptive services is one of several promising elements of High-Impact Practices (HIPs) in Family Planning [6]. LARCs, like IUDs and implants, have higher efficacy and continuation among adolescents who choose them compared to short-acting methods [7][8][9]. Previous studies demonstrate that youth, including adolescents ages 15 to 19, will use a variety of methods, including LARCs, when offered a full range of choices in an enabling environment [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%